Teacher Motivation, Workload, and Retention in Azerbaijan’s General Education System: A Human Resource Management Perspective - Mahammad Azizi-Meshkin (Theoretical Hypotheses and Empirical Results, 2025)
Teacher motivation, workload, and retention are increasingly recognized as central determinants of education system quality and sustainability. While Azerbaijan has implemented substantial reforms in curriculum modernization, assessment mechanisms, and digital infrastructure within general education, comparatively limited attention has been paid to the human resource management (HRM) dimensions shaping teachers’ professional experiences. This article examines teacher motivation, workload, and retention in Azerbaijan’s general education system through an HRM perspective, drawing on international theoretical frameworks and secondary statistical evidence from OECD, UNESCO, the World Bank, and the International Labour Organization. The analysis reveals that excessive administrative workload, compliance-oriented performance management, limited career progression pathways, and uneven incentive structures undermine teacher motivation and increase retention risks, particularly among early-career and rural teachers. By reframing these challenges as systemic HR governance issues rather than individual shortcomings, the article proposes evidence-based policy and HRM reforms aimed at strengthening workforce sustainability, improving teacher motivation, and enhancing education quality in Azerbaijan.